ON ALGEBRAS OF BOUNDED FUNCTIONS ON COMPLETELY REGULAR SPACES - Karakhanyan, M.I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
Some aspects on strict topology in algebras of continuous and bounded functions on completely regular spaces are discussed in this work. Also some properties of their dual spaces are investigated.
Keywords: $β$-uniformly algebras; complete regular space; discontinuous multiplicative functional